Performance of two lettuce cultivars under different amounts of irrigation in protected environment - Souza, J. N. C.; Souza, J. B. C.; Passos, M. L. V.; Silva, F. A. O.; Rodrigues, K. M.; Farias, M. F. (Scientific Electronic Archives, 2019)
The scarcity of information on the demand of water for the cultivation of vegetables, such as lettuce, in protected environment, especially with regard to the adequate management of irrigation, limits productive performance. The objective of this study was to evaluate the effect of different irrigation slides on two cultivars of lettuce in protected environment. The experiment was conducted in Chapadinha - MA, from March to May 2017. The cultivars of lettuces used were Brava and cv. Grand Rapids-TBR, in a completely randomized experimental design with 5 treatments consisting of irrigation blades: 6,0, 12,0, 16,5, 19,5 e 31,8 mm corresponding to the tensions 6, 10, 15, 30, e 50 kPa, respectively, and five replications, totaling twenty five plots per cultivar. The following variables were analyzed: plant height, stem diameter, number of leaves, root volume, fresh shoot mass, shoot dry weight, fresh root mass, root dry mass and root length. For the cultivar Brava, the irrigation blade for tension of 50kPa, recorded the highest absolute yield of fresh and dry mass of the shoot, with averages of 65.99 g and 7.68 g, respectively. Likewise, for the cultivar cv. Grand Rapids-TBR, the 50 kPa strain also provided the highest numerical estimate for fresh and dry shoot mass, 129.09 g and 51.03 g, respectively. The blades corresponding to the tensions of 6 and 10kPa, consumed about 18 mm per plant more than the tension of 50 kPa, for both cultivars. In an equivalent way, the fresh mass of the aerial part had greater increase in the tension of 50 kPa (65.99 g).